A Critical Analysis of Scientific Productivity of an Institute, CSIR-NAL - Shivaram, B. S.; Sahu, Satya Ranjan; Dey, Satya Ranjan; Ramesha, B. (Journal of Information and Knowledge, 2016)
This paper describes results of a scientometric study of the Council for Scientific and Industrial Research - National Aerospace Laboratories (CSIR-NAL). The purpose of the study is to evaluate the research performance of CSIR-NAL in the last ten years. Data collected from leading citation database SCOPUS for the years 2005-2014. The findings indicate that in ten years, CSIR-NAL has published 1002 research papers in peer reviewed sources. Science cluster divisions had published more numbers of papers than engineering cluster though they are in small numbers. Total 667 papers had received citations and 712 papers were published in impact factor journals.